كتاب ((الجديد في اللغة العربية)) -الجزء الثاني لتعليم اللغة العربية للطلاب الصينيين : دراسة تحليلية تقويمية - ليو، ري فين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The main purpose of this research is to understand the quality of book “Aljadid fi allughtu alarabiyah – Volume Two” prepared for Chinese students in China. The research was based on the world standards to evaluate the book in question used for the intermediate level in Chinese institutes. The research looks into the book's linguistic, cultural, and educational contents, how it contributes to improving Arabic language teaching in China, and finally provides recommendations to improve the textbook used there. The research explains the status of teaching Arabic language in China in general, discusses the specifications of a good textbook and the foundations needed to teach Arabic language, and the criteria for evaluating Arabic educational textbooks used for non-natives based on the recommendations of Dr. Rushdi Ahmad Tu'eimah in his book, after making modification to some of its elements to suit this research. The book earned a total of 72%, which is equivalent to a good estimation using the 'Microsoft Excel' computer program. Based on this estimation, the research concludes that the content of the book is suitable for Chinese students in teaching Arabic language for non-natives with regard to linguistic and educational aspects; the book still needs improvement in its cultural content and technological learning. However, Teachers, when using this book should avoid using translated language in teaching vocabulary, grammar and so on, rather they should provide various linguistic activities by using modern teaching methods. It is also essential that the book be accompanied by Arabic language dictionary, CD for the teachers, and exercise pamphlets.